(untitled) (Global Media Journal - German Edition, 2011)
The election in Iran 2009 caused a serious crisis in Iranian society. The news media around the world reported about alleged manipulation, election fraud and other irregularities. “Where is my vote?” became the rallying cry of Iran’s opposition. This paper presents a cross-national comparative media analysis of news reporting on the Iranian election and the subsequent national and international reactions. It focuses on how a controversial political event was covered by two of the world’s leading television news broadcasters: Al Jazeera Arabic and CNN International, with a particular focus on Al Jazeera. Two theoretical frameworks were adopted: a contra-flow approach – Al Jazeera as an alternative source of news – as well as its role with respect to democratization. Two flagship news programs were analyzed over a six-week period in summer 2009. With quantitative framing analysis as the central methodology (using statistical factor analysis), we focused on the content of 66 television news stories.